2017
DOI: 10.1007/s13167-017-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics in the treatment of mood disorders: Strategies and Opportunities for personalized psychiatry

Abstract: Personalized medicine (personalized psychiatry in a specific setting) is a new model towards individualized care, in which knowledge from genomics and other omic pillars (microbiome, epigenomes, proteome, and metabolome) will be combined with clinical data to guide efforts to new drug development and targeted prescription of the existing treatment options. In this review, we summarize pharmacogenomic studies in mood disorders that may lay the foundation towards personalized psychiatry. In addition, we have dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 127 publications
1
63
0
2
Order By: Relevance
“…Moreover, our exploratory analysis suggested that (1) SIRT1 variants influence some inflammation parameters, such as the IL-1β level (after PMA induction) which has been repeatedly associated with depression and other psychiatric diseases [32, 33]; and (2) RORA variants modulate both PMA-induced IL-6 and IL-12 and unstimulated serum levels of IL-6 and VCAM1. Neuroinflammation is thought to contribute to the pathogenesis of AD, with active central nervous system trafficking of immunoregulatory cells necessary for amyloid clearance and mitigation of the neuroinflammatory response [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our exploratory analysis suggested that (1) SIRT1 variants influence some inflammation parameters, such as the IL-1β level (after PMA induction) which has been repeatedly associated with depression and other psychiatric diseases [32, 33]; and (2) RORA variants modulate both PMA-induced IL-6 and IL-12 and unstimulated serum levels of IL-6 and VCAM1. Neuroinflammation is thought to contribute to the pathogenesis of AD, with active central nervous system trafficking of immunoregulatory cells necessary for amyloid clearance and mitigation of the neuroinflammatory response [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although personalized treatment of non-perinatal depression has integrated recent research on biomarkers and genetics, especially in the choice of antidepressants,12 our understanding of the genetics and biomarkers of perinatal mood disorders is still in the early stages. Some of the most frequently implicated genes, including 5-HTT ,13 OXTR ,14 COMT ,15 MAOA ,16 and HSD11B1 ,17 have been assessed in a recent systematic review 18.…”
Section: Introductionmentioning
confidence: 99%
“…2 Even though most psychiatric drugs show benefits over placebo in clinical trials, nearly 75% of psychiatric prescriptions do not successfully treat the patient's condition. 3,4 Low drug efficacy for individual patients suggests a critical need to improve treatment prioritization for psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%